What characterises high-growth firms in South Africa? Evidence from World Bank Enterprise Survey - A. Mthimkhulu; M. Aziakpono (South African Journal of Business Management, 2016)
In the past two decades, considerable efforts have been made to promote small and medium enterprises as a catalyst for job creation in many countries, including South Africa. However, globally a growing body of evidence shows that only a small segment of small and medium enterprises in an economy accounts for 50 to 70% of net new jobs. Using the World Bank Enterprise Survey and logit and quantile regressions, this paper empirically explores the characteristics of high growthfirms in South Africa. The study finds that firms that are less than 6 years create more jobs than the average firm in the sample. The results further suggest that the typical high-growth firms are black-owned.
Keywords: 650